"Estrato de senhores": aspectos políticos da Guarda Nacional na província do Espírito Santo (1831-1873) - Oliveira, Kamyla Nunes de Deus (2014)
Given the need to analyze accurately the role of the National Guard in the provinces of the Empire, this paper proposes the study of this institution in the Province of the Espírito Santo, in the period 1831-1873. With an approach that incorporates new approaches political history, pretend to understand the joints that were forged within the National Guard. Trying to identify the "stratum of Lords", which speaks Uricoechea (1978), who commanded the citizen militia in the Espírito Santo nineteenth century, as well as outlining the political importance they had and observing how they contributed to the construction of the Imperial State. Having as sources Reports of Presidents of the Province (1831-1873), the registry's Matching Government on the National Guard (1846-1871), the registration of patents promotion (1848-1863), registration of patents GN (1863-1873), Official Record of Correspondence with the Supreme Commander of the National Guard (1869), the Record of Correspondence with the Supreme Commander of the South, North and Center (1870), the Registration of National Guard officers (from 1852 to 1880 ).